Laparoscopic treatment of ovarian tumors - Figueroa Zevallos, Víctor (2015)
This review tries to determine the efficiency and safety of minimally invasive surgery in the management of large benign ovarian tumors as well as to specify the ovarian cancer stage where the laparoscopic route is feasible and safe. We review ultrasound, Doppler color and CA 125 level studies done to differentiate benign from malignant tumors. A minimally invasive approach called laparoscopically-guided minilaparotomy is proposed for treatment of large benign tumors following oncologic surgery guidelines. Conservative managing in borderline tumors and early ovarian cancer in women who want to preserve fertility as well as complete laparoscopic staging are also considered. We conclude laparoscopy is the best route for benign ovarian tumors treatment, including larger than 10 cm cysts. Minimally invasive surgery is possible in borderline and early ovarian cancer, in selected patients and performed by surgeons with oncology training and advanced laparoscopy skills.